Innovative Governance dalam Penerapan Smart Village sebagai Upaya Peningkatan Kesejahteraan Masyarakat: Studi Kasus: Desa Kutuh, Kecamatan Kuta Selatan, Kabupaten Badung - I Gede Krisna Yudandi; I Dewa Ayu Putri Wirantari; Juwita Pratiwi Lukman (Jurnal Media Administrasi, 2024)
Kutuh Village has succeeded in providing a change from a poor village to one of the richest villages in Indonesia, showing the commitment of the Kutuh Village Government in developing villages. However, some problems that occur such as community awareness, village funding design and human resources in each element. With a study using innovative governance indicators from Tahir (2016: 284). This type of research is descriptive qualitative. The determination of informants is carried out by purposive techniques and snowball sampling. Data analysis is carried out by reduction, presentation of data and drawing conclusions. The results of the study show that the implementation of Smart Village in Kutuh Village has succeeded in achieving innovative governance. However, it needs to be optimized again on indicators of community participation Recommendations that can be given are optimizing community empowerment programs and changing policies regarding the implementation of smart villages in Kutuh Village.